STRATEGI PENGOPTIMALAN PENCAPAIAN PROGRAM UPAYA PENINGKATAN PENDAPATAN KELUARGA SEJAHTERA - utami, bunga chintia (Jurnal Niara, 2017)
Poverty in underdeveloped countries are characterized by rapid population growth. In Indonesia, the government's role in population to be submitted to the National Population and Family Planning (BKKBN). One of the programs is to Increase Revenue BKKBN Family’s Welfare (UPPKS). From 2010 to 2013 a decrease in the number of groups UPPKS. Based on the problems identified factors researchers focused on strength (strength), weakness (weakness), chance (opportunity) and threats (threat) in order to optimize the achievement of program outcomes UPPKS the Directorate. The purpose of the study was to look at factors weaknesses, strengths, threats and opportunities and choosing the right strategy to optimize the achievement of program UPPKS. The method used is the SWOT and AHP. The results showed the best strategy is derived from the power factor and the opportunities (SO): (1) take advantage of the availability of technical guidance for the development of work by local partners; (2) maximizing the data base to cooperate with other agencies that have programs that are compilance empowerment; (3) utilizing the integrated use of the website to attract cooperation as a form of technological development and utilization of information. Utilizes the integrated use of the website to attract cooperation is priority.